Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution - Justice, Anne E.; Karaderi, Tugce; Highland, Heather M.; Young, Kristin L.; Graff, Mariaelisa; Lu, Yingchang; McCarthy, Mark, I (Nature Portfolio, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF >= 5%) and nine low-frequency or rare (MAF < 5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Genome-Wide Association; Type-2 Diabetes Susceptibility; Adipose-Tissue; Kinase 7; Adipocyte Differentiation; Rs11209026 Polymorphism; Abdominal Adiposity; Waist Circumference; Insulin-Resistance; Receptor Alk7